Assessment of grip force control in patients with muscular dystrophy - Kurillo, Gregorij (Zdravniški vestnik, 2004)
Background: The majority of hand functionality tests are based on qualitative assessment which largely depends on the experience of the therapist. Computer-assisted methods can provide more objective and accurate measurements of the grip force and other parameters related to grasping. Methods: We analysed the grip force control in 12 patients with muscular dystrophy using the tracking system developed. The system consists of a grip-measuring device with end-objects assessing the force applied in different grips. The device was used as input to a tracking task where the patient applied the grip force according to the visual feedback from the computer screen. Each patient performed two tasks which consisted of tracking a ramp and sinus target. Results: We analysed the maximal grip force as assessed in the ramp task and the tracking accuracy of the sinus task. The results are compared among five different grips (cylindrical, lateral, palmar, pinch and spherical grip), applied with dominant and non-dominant hand. The results show no significant difference in tracking accuracy between the dominant and non-dominant hand. Conclusions: The results obtained in tracking the ramp target showed that the method could be used for the assessment of the muscle fatigue, providing quantitative information on muscle capacity. The results of the sinus-tracking task showed that the method can evaluate the grip force control in different types of grips, providing information on hand dexterity, muscle activation patterns or tremor.
Keywords: funkcionalnost; mišična distrofija; prijemanje; rehabilitacija; roka; sila prijema